Paratesticular Adipocytic Neoplasms Evaluated at a Single Institution. (11th September 2019) - Mustafa, Mohamed; Priemer, David; Idrees, Muhammad; Chen, Shaoxiong
Abstract: Objectives: Some of the scrotal masses are extratesticular neoplasias and develop from paratesticular tissues. Paratesticular region has a complex anatomy and contains epididymal and testicular appendages as spermatic cord, testicular tunicas, epididymis, and vestigial remnants. Therefore, neoplasms originating from this region comprise a heterogeneous group of tumors. Herein, we document paratesticular adipocytic neoplasms and the patient's mean age and the mean size of tumor at presentation. Methods: We retrospectively searched our database for paratesticular adipocytic neoplasms from the year 2001 to 2015. A total of 47 cases were identified and reports were reviewed. Results: Of the total 47 cases, 28 (60%) spermatic cord lipomas, 9 (19%) well-differentiated liposarcomas, and 10 (21%) dedifferentiated liposarcomas were identified. The mean age for presentation for these diseases was of 41, 59, and 68 years, respectively. Conclusion: The most common paratesticular adipocytic neoplasm in our institution is spermatic cord lipoma (60%), occurring in younger age group (mean age 40 years). However, up to 40% cases are malignant and include well-differentiated and dedifferentiated liposarcoma, occurring at a relatively older age population (59 and 68, respectively).